2010
DOI: 10.5130/ajceb.v10i1/2.1582
|View full text |Cite
|
Sign up to set email alerts
|

Influences on Women’s Choices of Careers in Construction: A South African Study

Abstract: This paper analyses the factors influencing the choices of careers in construction by South African women. The literature on challenges which influence women's choices of careers in construction was reviewed and questionnaires were conducted with multiple samples, including construction organisations, construction students and professional women working in construction. The study found that women have a role to play in the construction industry and that they can build successful careers within the sector. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 7 publications
0
11
1
Order By: Relevance
“…From the findings of the survey, although the percentage of female employers to their male counterparts is approximately 16%, it was concluded that women in the construction industry are being accorded equal opportunities in the Nigerian construction industry. However, this finding is not in agreement with Madikizela and Haupt (2005) where a survey was carried out on the South African construction industry women. In the research, 94.1 percent of women said women do experience discrimination on the job in the construction industry while about 76.5 percent opine that this discrimination is more prevalent on construction sites than in consultancies films.…”
Section: Equality Of Opportunities Amongst Male and Females In The Nicontrasting
confidence: 87%
“…From the findings of the survey, although the percentage of female employers to their male counterparts is approximately 16%, it was concluded that women in the construction industry are being accorded equal opportunities in the Nigerian construction industry. However, this finding is not in agreement with Madikizela and Haupt (2005) where a survey was carried out on the South African construction industry women. In the research, 94.1 percent of women said women do experience discrimination on the job in the construction industry while about 76.5 percent opine that this discrimination is more prevalent on construction sites than in consultancies films.…”
Section: Equality Of Opportunities Amongst Male and Females In The Nicontrasting
confidence: 87%
“…Both the Indian and people-of-colour demographics have considerably lower representations, with the Indian group slightly ahead of the people-of-colour group. The dominance of White PrQs might be rooted in historical privileges associated with apartheid, where educational and professional opportunities were skewed in favour of the White population [6,34]. The relatively lower representation of African, Indian, and professionals of colour could suggest the existence of barriers-either educational, socioeconomic, or systemic within the profession.…”
Section: Distribution Of Professionally Registered Quantity Surveyors...mentioning
confidence: 99%
“…The presence of senior professionals (e.g., "55-59" and "60-64") across racial groups indicates an opportunity for mentorship programs, helping younger professionals navigate the field. The distribution, especially the prominence, of the White professionals in the "45-49" age bracket, might reflect the historical advantages that this group had in education and professional opportunities during their early career stages in South Africa [34,40].…”
Section: Demographics-based Impediments To Professionalism In the Sou...mentioning
confidence: 99%
“…In fields where men predominate, men have more resources and influence to enact discriminatory practices, ideologies, and laws (Damaske, 2011). The continued absence of visible and effective strategies to empower women in organizations could be attributed to male-dominated and sexist management practices (Hicks, 2012;Madikizela, 2010). Women in the construction industry, for instance, reported that there was not enough money available to raise the status and skills of female workers (Cha, Y, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%